A Study of Stall Condition of a Centrifugal Compressor based on CFD and Experimental Methods. Issue 1 (February 2021) - Wang, R.; Wang, H. L.; Yang, S. H.; Tan, J. J.; Jiang, S.; Ren, J.Q.
Abstract: The stall point of a centrifugal compressor is obtained by CFD method and FFT method, and an experiment in the stall point is carried out. Firstly, the curves of the compressor efficiency and total pressure ratio with flow rate are obtained by the steady CFD analysis. Secondly, according to the curves, the unsteady CFD analysis and frequency signal analysis are carried out at the operation points where stall may occur. Then the stall point of the compressor is obtained. On the basis of the results of numerical analysis, the model machine is used to carry out the test. By comparing the results of the numerical method and the experimental method, the stall is identified at the similar operation point, which proves the effectiveness of the prediction method in this paper.